2020
DOI: 10.1159/000505151
|View full text |Cite
|
Sign up to set email alerts
|

Finasteride and Suicide: A Postmarketing Case Series

Abstract: Background: In 2011, depression was added to the product labeling of finasteride in the USA. The US Food and Drug Administration's Adverse Event Reporting System database contains at least 36 death cases for finasteride. The aim of this study is to characterize the clinical histories and symptoms reported by a series of 6 suicide victims who took finasteride for treatment of androgenic alopecia. Methods: Medical records and autopsy reports were provided by family members of the cases. Relevant information was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…For example, the disproportional signals of adverse events in association with finasteride use could result from adverse effects, such as persistent sexual dysfunction, having a greater toll on younger patients using finasteride to treat a nonurologic condition . This hypothesis is supported by a small postmarketing case series of 6 suicide completers who took finasteride for the treatment of androgenic alopecia . Among all 6 cases, investigators found evidence of persistent sexual dysfunction after discontinuation of finasteride treatment.…”
Section: Discussionsupporting
confidence: 72%
“…For example, the disproportional signals of adverse events in association with finasteride use could result from adverse effects, such as persistent sexual dysfunction, having a greater toll on younger patients using finasteride to treat a nonurologic condition . This hypothesis is supported by a small postmarketing case series of 6 suicide completers who took finasteride for the treatment of androgenic alopecia . Among all 6 cases, investigators found evidence of persistent sexual dysfunction after discontinuation of finasteride treatment.…”
Section: Discussionsupporting
confidence: 72%
“…Biological studies have shown that finasteride crosses the blood–brain barrier and can be involved in mood changes by affecting the concentration of neuro-steroids and their metabolites in the cerebrospinal fluid 15 – 18 . Psychiatric and suicidal events can appear early after treatment initiation 13 , 14 and persist long after treatment discontinuation, as described in the “post-finasteride syndrome”, consisting of an association of sexual, physical, and psychological symptoms that develop during or after finasteride exposure and persist after discontinuation 7 , 19 . Regarding psychological symptoms, clinically significant depression was reported in 50% of a sample of men with post-finasteride syndrome, and anxiety in 34% 20 .…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] Furthermore, a recent study revealed that finasteride can cause adverse effect on mental health and increases the risk of suicidality and depression. [ 4,5 ]…”
Section: Introductionmentioning
confidence: 99%
“…[3] Furthermore, a recent study revealed that finasteride can cause adverse effect on mental health and increases the risk of suicidality and depression. [4,5] To overcome these side effects caused by oral administration of finasteride, minoxidil, a topical alopecia drug, has been developed and widely used in clinics. However, minoxidil topical formulations experience difficulty in delivering the drug to the deep hypodermic region (>700 ÎŒm), where hair follicles are located, against the skin barrier.…”
Section: Introductionmentioning
confidence: 99%